THE NATURE AND LEGAL BASIS OF CITIZEN PARTICIPATION IN ENVIRONMENTAL DECISION-MAKING - Buzrukhoja Khairullaevich Mamadaliev (Journals Park Publishing, 2024)
This article discusses the ecological rights of citizens, ecological interests, the basis and importance of their participation in environmental decision-making, as well as the solutions and foundations of ensuring the rational use of natural resources.
Keywords: state bodies, citizen, public associations, decision, right, interest.